Concordance and Consensus Indicators of Four Measures of Readability - Tan, Soon Hock (Journal of Modern Languages, 2017)
The focus of this paper is on considering the importance of the reading skills by considering four aspects, as: (i) the importance of the reading skill, (ii) the significance of being aware of individual differences and how to cater for them in reading; (iii) by implication, the indispensable role of the language teacher in choosing suitable reading materials with or without the help of subject specialists; (iv) the role of content specialists in selecting materials of suitable readability levels in the Malaysian education environment.